Identifikasi Bangunan Cagar Budaya Sebagai Media Belajar Siswa di Kota Metro Lampung - Lestari, Riska Dwi; Karsiwan, Karsiwan (Asatiza: Jurnal Pendidikan, 2024)
The purpose of this research is to identify historical places in Metro city as learning for students in developing intellectual character, increasing students' awareness of local history, integrating local history in history subjects, and using local resources as learning resources. This research is a type of descriptive qualitative research in which it is a method of collecting new data and information. Data were obtained by collecting various literature sources such as books, journals, interviews, and online research articles that are in accordance with the research problem. The results show that learning facilities are very helpful in teaching and learning activities, such as nature reserve buildings. The nature reserve building is a built structure which is composed of natural and man-made objects. So that later it can meet the needs of both walled and non-walled and roofed rooms. And students will know more about the history of cultural heritage and be able to practice it in everyday life.